Triebelina indopacifica and Triebelina porinetia sp. nov. (Ostracoda) from French Polynesia and first insight into their pore systems - Forel, Marie-Béatrice (Zootaxa, 2024)
The present contribution documents the occurrence of Triebelina indopacifica van den Bold around Moorea and Tahiti, Windward Islands, French Polynesia and describes the new species Triebelina porinetia sp. nov.. The morphology of numerous specimens attributed to A-1 and A-2 juvenile stages of Triebelina indopacifica is thoroughly described, allowing the first insights into its ontogeny. With the aim to unravel the significance of poorly exploited characters in their taxonomy and systematics, the pore systems of Triebelina indopacifica and Triebelina porinetia sp. nov. are described. Patterns are recognized through the specimens and homologous pore systems characterizing the studied Triebelina species are proposed. The distribution of pore systems on the lateral surface of Triebelina therefore appears of generic significance, while indications at the species level may be sought in the morphology of rims of rimmed pores, as well as of marginal spines.